FOUND IN TRANSLATIONS: J.V. SNELLMAN’S (1806–1881) THOUGHTS ON TRANSLATIONS AS A WAY TO STRENGTHEN THE FINNISH NATIONAL LITERATURE - Mäkinen, Ilkka (Knygotyra, 2016)
Until the 1840s, the dominating language in Finland was Swedish, even if ca. 80 per cent of the population had Finnish as mother tongue. The administration, academic life, public matters and literary life were conducted in Swedish. The literature in Finnish was limited mostly to the religious domain, basic legislation and books of rudimentary instruction for agriculture and medicine, one or two newspapers and journals. The situation started to change in the 1840s, with the birth of the Finnish national movement. One of the most important actors in this movement was the philosopher, journalist and statesman Johan Wilhelm Snellman (1806–1881). This article presents his views on how translations from foreign languages can be used to form a Finnish national literature. His views in this matter were closely related to his theoretical philosophy that was heavily influenced by Hegel. Snellman demanded that the Swedish-speaking elite should change its language into Finnish, and create a high-class Finnish-language national literature of scholarly books and belles-lettres. Translations from foreign languages would give standards for Finnish writers and build contacts to the general European literature and culture. He initiated in 1870 a translation program that was managed by the Finnish Literature Society.
Keywords: Johan Wilhelm Snellman (1806–1881); Finland; 19th century; cultural history; translations; Finnish national movement; Fennomans; Finnish literature